Clinical Risk Score for Predicting Vascular Dementia after Ischemic Stroke in Thailand - Pornpatr A. Dharmasaroja; Thammanard Charernboon (Stroke Research and Treatment)
Background. Poststroke dementia is an important consequence of stroke and warrants early prevention, detection, and management. The objective of the study was to develop a simple clinical risk score for predicting risk of vascular dementia in patients with ischemic stroke. Methods. The design was a prospective cohort study with 177 ischemic stroke survivors. A standard stroke evaluation was performed at admission, and dementia evaluation was conducted at six months after stroke. The significant predictors were used to develop a risk score using a multivariable logistic regression model. Results. Six months after stroke, 27.1% of the patients were diagnosed with vascular dementia. Five predictors were used in the risk score: age, education, history of stroke, white matter hyperintensities, and stroke subtype. The risk score had an area under receiver operating characteristic curve (AuROC) of 0.76, 72.9% sensitivity, and 79.1% specificity in predicting risk of vascular dementia. The predicted probability of vascular dementia for each risk score point was also reported. Conclusion. The clinical risk score had an acceptable accuracy in predicting vascular dementia in ischemic stroke survivors. It can be used for identifying those who are at a high risk of developing vascular dementia.